2021
DOI: 10.3390/ijms222413656
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Peptides in Asthma

Abstract: Numerous regulatory peptides play a critical role in the pathogenesis of airway inflammation, airflow obstruction and hyperresponsiveness, which are hallmarks of asthma. Some of them exacerbate asthma symptoms, such as neuropeptide Y and tachykinins, while others have ameliorating properties, such as nociception, neurotensin or β-defensin 2. Interacting with peptide receptors located in the lungs or on immune cells opens up new therapeutic possibilities for the treatment of asthma, especially when it is resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 255 publications
(297 reference statements)
0
15
0
Order By: Relevance
“…Interestingly, as described before, several adipokines can directly suppress the HPT axis. However, numerous studies have clearly demonstrated how they can enhance (e.g., leptin or resistin) or alleviate (e.g., adiponectin and ghrelin), various features of inflammatory disease (e.g., asthma), acting either as pro- or anti-inflammatory factors, respectively [ 74 , 75 ]. Therefore, an indirect effect of adipokines mediated by inflammation may be also hypothesized.…”
Section: The Effects Of Adipose Tissue Dysfunction On Androgen Levelsmentioning
confidence: 99%
“…Interestingly, as described before, several adipokines can directly suppress the HPT axis. However, numerous studies have clearly demonstrated how they can enhance (e.g., leptin or resistin) or alleviate (e.g., adiponectin and ghrelin), various features of inflammatory disease (e.g., asthma), acting either as pro- or anti-inflammatory factors, respectively [ 74 , 75 ]. Therefore, an indirect effect of adipokines mediated by inflammation may be also hypothesized.…”
Section: The Effects Of Adipose Tissue Dysfunction On Androgen Levelsmentioning
confidence: 99%
“…In the analysis of the main polymorphism variants of the hBD-1 genes rs1047031 (C/T), rs1799946 (C/T), rs2738047 (C/T) and rs11362 (C/T) by genotyping 575 blood samples of men and women, cigarette smokers (288)/non-smokers (287), it was found that the CT and CT+TT rs1799946 genotypes showed a 5-fold increased correlation among smokers compared to control women, but with protective effects in the TT genotype in non-smokers [ 239 ]. In this regard, when analyzing the level of hBD expression in asthma, it is necessary to take into account the possibility of genetic polymorphisms of AMP genes, which can aggravate the course of asthma [ 240 ]. Asthma is also associated with polymorphisms not only in the hBD-1 gene, but also in the hBD-2 gene.…”
Section: Allergenic Activity Of Ampsmentioning
confidence: 99%
“…Airway inflammation in asthma patients could be transmitted to the central nervous system resulting in the secretion of mediators in the airway nerves, which could play critical roles in neuroimmune interactions and worsen airway inflammation. 28 Furthermore, psychological disorders, such as depression and anxiety, could exacerbate asthmatic bronchoconstriction by altering the function of the brain's regions involved in respiratory control. 29 These observations thus suggest that nerves could be involved in the modulation of asthmatic airway events, as the brain must transmit stress-and mood-related stimuli from the environment, hence signaling inflammatory mechanisms in the lungs and exacerbating the underlying disease.…”
Section: Economic Burden Of Asthmamentioning
confidence: 99%